Pseudoaneurysm after total arch replacement mimicking malignant lymphadenopathy. Issue 7 (19th August 2020) - Chiba, Yosuke; Yamasaki, Kei; Ikegami, Hiroaki; Yatera, Kazuhiro
Key message: Pseudoaneurysm should be considered in the differential diagnosis when the computed tomography (CT) findings show a mediastinal mass in patients with a history of cardiovascular surgery even if such surgery occurred over two decades previously. Abstract : Pseudoaneurysm should be considered in the differential diagnosis when the computed tomography (CT) findings show a mediastinal mass in patients with a history of cardiovascular surgery even if such surgery occurred over two decades previously.